Early strength gains in eccentric hip adduction and adduction-to-abduction ratio following an 8-week Copenhagen Adduction Exercise in elite adolescent taekwondo athletes - Unuvar-Yuksel, E.; Bozgeyik-Bagdatli, S.; Bazancir-Apaydin, Z.; Guney-Deniz, H. (Journal of Bodywork and Movement Therapies, 2025)
Objective The Copenhagen Adduction Exercise (CAE) has been studied in football players to determine its impact on strength gains. We aimed to examine the effects of the CAE on eccentric hip adduction (EHAD) strength and the eccentric adduction-to-abduction strength ratio in elite adolescent taekwondo athletes.